2011
DOI: 10.1097/eja.0b013e32834296d5
|View full text |Cite
|
Sign up to set email alerts
|

Propofol post-conditioning protects against cardiomyocyte apoptosis in hypoxia/reoxygenation injury by suppressing nuclear factor-kappa B translocation via extracellular signal-regulated kinase mitogen-activated protein kinase pathway

Abstract: Propofol exerts cardioprotection when administered at the early phase of reperfusion. The effect is mediated through decrease in cardiomyocyte apoptosis and NF-κB nucleus translocation potentially via ERK signalling pathways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
5
24
0
Order By: Relevance
“…Prepared propofol was added to the medium at different concentrations of 0, 25, 50 or 100 µM for 30 min prior to IHR exposure, and kept in the medium throughout the entire experiment. This dose range for propofol was selected from a previous study and considered as the range of concentrations that was clinically relevant (15). Cells that were not treated with either propofol or IHR were used as a control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Prepared propofol was added to the medium at different concentrations of 0, 25, 50 or 100 µM for 30 min prior to IHR exposure, and kept in the medium throughout the entire experiment. This dose range for propofol was selected from a previous study and considered as the range of concentrations that was clinically relevant (15). Cells that were not treated with either propofol or IHR were used as a control.…”
Section: Methodsmentioning
confidence: 99%
“…An in vitro study has demonstrated that propofol post-conditioning inhibits the activation of NF-κB induced by hypoxia/reoxygenation and protects cardiomyocytes against apoptosis (15). Other studies reported that propofol suppresses the activation of HIF-1 induced by lipopolysaccharides or hypoxia in macrophages (24), alveolar epithelial cells (25) and lung epithelial cells (22).…”
mentioning
confidence: 99%
“…The potential molecular mechanisms include antioxidation, anti-inflammation, or activating cardioprotective signaling pathways [1012]. However, little is known about the direct upstreaming target or initiating molecule.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, insulin resistance is generated or aggravated (29,32,33). Previous studies have demonstrated that propofol inhibits NF-κB activity in various tissues or cells (34)(35)(36)(37)(38). Therefore, it was hypothesized that the protective effect of propofol against TNF-α-induced insulin resistance in primary mouse hepatocytes may be associated with the inhibitory effect of propofol on the NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 99%